A scoping method for human performance integrity and reliability assessment in process industries. Issue 4 (11th May 2021) - Kyriakidis, Miltos; Dang, Vinh N.
Abstract: An approach to manage human performance related risks in petrochemical sector is to use human reliability analyses (HRA) techniques. However, the focus of HRAs on individuals and on decomposed tasks overlooks the likelihood that collective actions and behaviors might lead to system failures. This study introduces an alternative approach, referred to as Human Performance Integrity (HPI) index, to assess human performance conditions on the whole, as they relate to safety, in petrochemical facilities. Additionally, the approach is used to rate installations in terms of their defenses against safety‐relevant human failures. The HPI index is built upon the notions of Cognitive Reliability and Error Analysis Method. By means of a 42‐question survey, data was collected on the factors that improve or reduce human performance in 11 oil refineries. Data was used to assess the facilities' safety performance. Results were compared against information obtained from relevant investigation reports, as well as and an independent evaluation of the facilities carried out by certified auditors. Findings support the use of HPI index from novice and experienced scholars and/or practitioners as a quick and effortless, yet sound and efficient manner to assess safety and reliability performance of oil refineries from a human factors perspective.